Aluminium Alloys and Composites - Omar Cooke, Kavian (IntechOpen, 2020)
Aluminium (Al) is a metal of great importance because of its excellent corrosion resistance, high electrical and thermal conductivity, good reflectivity, and very good recycling characteristics. The properties of heat-treatable Al-alloys can be further enhanced by the inclusion of a reinforcing phase that increases the mechanical properties of the overall composite. This book is a comprehensive guide on the different types of aluminum alloys and the new advances that have been made in developing and manufacturing aluminum alloys and composites. This text provides a comprehensive overview of the processing, formability, and chemical composition of aluminum alloys and composites. Part One is focused on evaluating the types and properties of advanced aluminum alloys and composites, while Part Two explores characterization. The advantage of this book is that it provides a detailed review of major advances that have occurred in the development and application of aluminum alloys and composites while outlining a development strategy for these materials.